Manajemen Marketing Digital Untuk Meningkatkan Daya Beli Konsumen - DATIN NADLIROH, INDAH; ANI PRAYEKTI, ROSI (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
This research aims to show the importance of implementing well-organized management functions so that companies can minimize the occurrence of bad risks. Thus, to support several stages in the management structure, competent human resources are needed. To be able to compete and create different characteristics and become a symbol in the company. The success of the company can improve its performance and can be supported by the work environment and work ethic owned by each employee.